The Effectiveness of Multicultural-Based PAI Student Worksheets (LKPD) as a Media for Internalizing the Value of Rahmatan lil 'alamin - prasetyo Nursalim; alif ma'fudin; rizquna salma labibah; raihan hisyam; purwoko (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to describe the effectiveness of the multicultural-based Islamic Religious Education (PAI) Student Worksheet (LKPD) as a medium for internalizing the value of raḥmatan li al-'ālamīn in the learning process. This research departs from the need for PAI teaching materials that not only convey cognitive material, but are also able to foster an attitude of tolerance, respect for diversity, and an understanding of inclusive Islamic values. The research approach used is qualitative with a case study design so that the researcher can delve deeply into the students' learning experience, class interaction, and the process of internalizing values through the use of LKPD. The data collection method was carried out through participatory observation, in-depth interviews with teachers and students, open questionnaires, and analysis of learning-related documents. Data were analyzed using the Miles & Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that multicultural-based LKPD PAI effectively supports the internalization of the value of raḥmatan li al-'ālamīn. This effectiveness can be seen through increased tolerance, the ability to understand differences, the ability to work together across backgrounds, and a more inclusive pattern of class interaction. Teachers also stated that LKPD helps facilitate multicultural discussions and provide a more contextual learning experience. This research is useful for the development of PAI teaching materials that are able to instill the value of religious moderation, as well as become a practical reference for educators in designing multicultural-based learning in various school settings.